Systematic review of influenza vaccine effectiveness against laboratory-confirmed influenza among older adults living in aged care facilities - Aye Moa; Mohana Kunasekaran; Zubair Akhtar; Valentina Costantino; C. Raina MacIntyre (Human Vaccines & Immunotherapeutics)
We estimated the effectiveness of influenza vaccines in preventing laboratory-confirmed influenza among older adults in aged care. Electronic database searches were conducted using search terms, and studies were selected as per the selection criteria. Fourteen studies were included for final review. The studies exhibited considerable variation in reported vaccine effectiveness (VE) across different seasons. Among the observational studies, VE ranged from 7.2% to 89.8% against laboratory-confirmed influenza across different vaccines. Randomized clinical trials demonstrated a 17% reduction in infection rates with the adjuvanted trivalent vaccine. The limitations include the small number of included studies conducted in different countries or regions, varied seasons, variations in diagnostic testing methods, a focus on the A/H3N2 strain, and few studies available on the effectiveness of enhanced influenza vaccines in aged care settings. Despite challenges associated with achieving optimal protection, the studies showed the benefits of influenza vaccination in the elderly residents.